Masa Kerja dan Lama Kerja Berhubungan dengan Keluhan Nyeri Punggung Bawah Pada Pengemudi Ojek Online - Sunarya, Putri Amelia; Chairani, Aulia; Hardini, Niniek; Bustaman, Nurfitri (Jurnal Ilmiah Kesehatan Masyarakat : Media Komunikasi Komunitas Kesehatan Masyarakat, 2024)
Background: Low back pain in Indonesia is the second highest illness after influenza. About 63 million (37%) Indonesians experience complaints of low back pain (LBP). NBP is a common problem in workers, including online motorcycle taxi drivers. Working positions that require online motorcycle taxi drivers to sit and support their body weight with vertebrae muscles and bones can cause muscle stiffness and spasm of vertebrae muscles, especially the lumbar part. Methods: Analytical quantitative research design using a cross-sectional approach. The sample of this study is an online motorcycle taxi driver with male gender, age 20-35 years and working > 3 months as an online motorcycle taxi driver, collected by consecutive sampling method. Result: Univariate results were obtained as much as NPB (60.2%), working >8 hours (61.3%) and working >1 year (64.5%). Bivariate results obtained a relationship between length of work (p value = 0.000) and tenure (p value = 0.000). Multivariate results show that the variable that most influences back pain complaints is the length of work (OR = 14.10). Conclusion: It is suggested that puskesmas frequently monitor and give counseling related to TB and the society clean their houses regularly and keep the house clean Keywords: low back pain, online motorcycle drivers, length of work, length of service